Implementation Of The Dick And Carey Model In Improving Islamic Religious Education Learning At Assalam Middle School Bandung (Qur'anic Inspiration Material In Preserving Nature) - Nugraha, Mulyawan Safwandy; Qodriani, Siti Hanna; Dedih, Ujang (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Students have an unfavorable perception of Islamic Religious Education as an academic subject taught in institutions. Islamic Religious Education is often associated with the notion that these lessons consist mainly of boring lecture-based teaching. The lecture approach, consisting mostly of verses from the Koran and Hadith in Arabic, often prevents students from actively participating in the lesson material. Therefore, researchers attempt to eliminate this negative connotation by applying the Dick and Carey model in the context of Islamic Religious Education, with special emphasis on the subject of